Pyridine Alkaloids from Senna multijuga As Acetylcholinesterase Inhibitors - Francisco, Welington [UNESP]; Pivatto, Marcos [UNESP]; Danuello, Amanda [UNESP]; Regasini, Luis O. [UNESP]; Baccini, Luciene R. [UNESP]; Young, Maria C. M.; Lopes, Norberto P.; Lopes, Joao L. C.; Bolzani, Vanderlan da Silva [UNESP] (Amer Chemical Soc, 2012)
As part of an ongoing research project on Senna and Cassia species, five new pyridine alkaloids, namely, 12'-hydroxy-7'-multijuguinol (1), 12'-hydroxy-8'-multijuguinol (2), methyl multijuguinate (3), 7'-multijuguinol (4), and 8'-multijuguinol (5), were isolated from the leaves of Senna multijuga (syn. Cassia multijuga). Their structures were elucidated on the basis of spectroscopic data analysis. Mass spectrometry was used for confirmation of the positions of the hydroxy groups in the side-chains of 1, 2, 4, and 5. All compounds exhibited weak in vitro acetylcholinesterase inhibitory activity as compared with the standard compound physostigmine.